Medical alternatives to oocyte donation in women with premature ovarian failure: a systematic review. (July 2013) - Robles, Ana; Checa, Miguel A.; Prat, Maria; Carreras, Ramón
Abstract Oocyte donation can satisfy the desire to have children in women with premature ovarian failure (POF) but little progress has been made to improve reproduction using the patients' own gametes. The aim of this study was to assess the effectiveness of alternative treatments to oocyte donation in patients with POF. A systematic search of MEDLINE, EMBASE and Cochrane databases from January1988 to January 2012 using descriptors related to POF, ovulation induction, and pregnancy was made. Randomized clinical trials of women with POF undergoing various treatments to achieve ovulation induction, often compared with alternative treatment and placebo groups, were only selected. Outcomes of interest were those related to pregnancy (biochemical and live birth). Twelve trials were included and analysed for methodology, inclusion and exclusion criteria, number of patients included, characteristics and type of intervention, and results in terms of ovulation rate, pregnancy rate and ongoing pregnancy rate. The large methodological variability among studies prevented to combined data for a meta-analysis. None of the studies showed statistically significant differences between the study groups. The lack of case-control studies with a placebo group makes it impossible to establish differences between a treatment and no treatment.